Influenza outbreak in a Canadian correctional facility. Issue 4 (July 2017) - Besney, Jonathan; Moreau, Danusia; Jacobs, Angela; Woods, Dan; Pyne, Diane; Joffe, A Mark; Ahmed, Rabia
Correctional facilities face increased risk of communicable disease transmission and outbreaks. We describe the progression of an influenza outbreak in a Canadian remand facility and suggest strategies for preventing, identifying and responding to outbreaks in this setting. In total, six inmates had laboratory-confirmed influenza resulting in 144 exposed contacts. Control measures included enhanced isolation precautions, restricting admissions to affected living units, targeted vaccination and antiviral prophylaxis. This report highlights the importance of setting specific outbreak guidelines in addressing population and environmental challenges, as well as implementation of effective infection prevention and control (IPAC) and public health measures when managing influenza and other communicable disease outbreaks.